Persistent Autonomic Engagement and Cardiac Control After Four or More Years of Autonomic Regulation Therapy Using Vagus Nerve Stimulation - Libbus, Imad; Premchand, Rajendra K.; Sharma, Kamal; Mittal, Sanjay; Monteiro, Rufino; Amurthur, Badri; KenKnight, Bruce H.; DiCarlo, Lorenzo A.; Anand, Inder S. (Frontiers in Physiology, 2022)
INTRODUCTION: Although heart failure (HF) outcomes have improved dramatically with the use of guideline directed medical therapy and implantable devices, the overall prognosis of patients with HF and reduced ejection fraction (HFrEF) remains poor. Autonomic Regulation Therapy (ART) using chronic vagus nerve stimulation (VNS) has been evaluated in the ANTHEM-HF study, using changes in heart rate (HR) dynamics as a biomarker of autonomic nervous system engagement and cardiac control to guide VNS titration. ART was associated with sustained improvement in cardiac function and HF symptoms in patients with HFrEF and persistent HF symptoms despite guideline-directed medical therapy (GDMT). We sought to determine whether the responsiveness of the autonomic nervous system to ART, as reflected in HR response to vagus stimulation during the VNS duty cycle, is maintained long-term chronic VNS administration. METHODS: Fifteen patients with HFrEF and implanted with a VNS systems in the ANTHEM-HF study were evaluated after 4.7  0.3 years (range: 4.0 - 5.0 years) of chronic ART. ECG electrodes were placed on each patient’s wrists, and ECG rhythm strips were recorded. Instantaneous heart rate (HR) time series was computed at each patient’s chronically programmed VNS intensity and during progressively increasing VNS intensity. HR during active stimulation (on-time) was compared to HR just prior to initiation of each stimulation cycle (off-time). RESULTS: Persistent autonomic engagement was observed in a majority of patients (11 of 15, 73%) after chronic ART for four or more years. The average magnitude of HR reduction during ART on-time in all patients was 2.4  3.2 bpm at the chronically programmed VNS pulse parameter settings. CONCLUSIONS: Autonomic responsiveness to VNS persists in patients with HFrEF who received chronic ART for up to 5 years as a supplement to GDMT. This suggests that the effects of ART on autonomic engagement and cardiac control remain durable over time.